2006
DOI: 10.1111/j.1442-2018.2006.00269.x
|View full text |Cite
|
Sign up to set email alerts
|

A nurse‐led rheumatology clinic’s impact on empowering patients with rheumatoid arthritis: A qualitative study

Abstract: The aim of this study was to describe a nurse-led rheumatology clinic's impact on empowering patients with rheumatoid arthritis (RA). Rheumatoid arthritis is a chronic, inflammatory disease that attacks many joints, causing considerable functional restrictions for patients. Consequently, these patients are dependent on a wide variety of health-care services. A descriptive, qualitative design inspired by phenomenography was chosen. The conceptions were collected through interviews with 16 strategically selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
117
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(128 citation statements)
references
References 27 publications
6
117
1
4
Order By: Relevance
“…Recent work has addressed this gap with two recent multi-centre studies undertaken in the UK of effectiveness and economic value [3] and, in France, of co-A c c e p t e d M a n u s c r i p t morbidity management [4]. Results provide robust evidence to support nurse-led clinics in the management of Rheumatoid Arthritis and co-morbidity detection with nurse-led clinics having higher 'general satisfaction' than physician-led clinics [5]. The findings of the UK multi-centre RCT were consistent with those from the only other large scale costs study -in the Netherlands -which demonstrated nurse-led clinics produced equivalent outcomes at lower unit cost [6,7] Recent work in Sweden also showed that patients undergoing biological therapy can be safely monitored more cost-effectively by a nurse-led Rheumatology clinic [8,9].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent work has addressed this gap with two recent multi-centre studies undertaken in the UK of effectiveness and economic value [3] and, in France, of co-A c c e p t e d M a n u s c r i p t morbidity management [4]. Results provide robust evidence to support nurse-led clinics in the management of Rheumatoid Arthritis and co-morbidity detection with nurse-led clinics having higher 'general satisfaction' than physician-led clinics [5]. The findings of the UK multi-centre RCT were consistent with those from the only other large scale costs study -in the Netherlands -which demonstrated nurse-led clinics produced equivalent outcomes at lower unit cost [6,7] Recent work in Sweden also showed that patients undergoing biological therapy can be safely monitored more cost-effectively by a nurse-led Rheumatology clinic [8,9].…”
Section: Discussionmentioning
confidence: 97%
“…However, apart from effectiveness, nurse specialist practice is underresearched and tends to be questionnaire-based and, hence, given the current lack of knowledge, unlikely to capture all factors influencing patient outcome. Moreover, although nurse specialists are able to draw on this research to articulate the value of their work, it seems they have more difficulty unpacking and describing the complexity of the care they give [5]. There are few observational studies of the processes of care in nurse-led clinics with studies, instead, favouring to evaluate outcomes and the patients' experiences.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore no surprise that nurse-led care was associated with increased patient knowledge. Patient education increases self-efficacy which in turn enables patients to take control of their arthritis (Arvidsson et al, 2006). It is surprising that these positive results of patient knowledge were not supported by those of coping with arthritis.…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…The nurse can obtain personal advice, as well as having contact with a doctor or other healthcare professional, when required. Patients have emphasized the nurse's role in coordinating the other team members (Arvidsson et al, 2006;Larsson et al, 2009). Eldh (2006) revealed that patients have a need to be listened to and to serve as a resource in the dialogue with the nurse.…”
Section: Discussionmentioning
confidence: 99%
“…The result of this study demonstrates that patients who encounter this holistic perspective experience improved well-being. The importance of the nurse devoting time to each individual patient, showing consideration and providing support has been illuminated and was also highlighted by Arvidsson (2006). According to Rycroft-Malone et al (2001), the key to a good relationship between the patient and the nurse is patient-centred care with continuity of contact.…”
Section: Discussionmentioning
confidence: 99%